Hubungan Sistem Antrian dan Optimalisasi Layanan Kesehatan terhadap Kepuasan Pasien pada UPTD Puskesmas Cipayung Kota Depok Tahun 2024: Association of Queueing System and Health Service Optimization with Patient Satisfaction at UPTD Cipayung Health Center, Depok City, 2024 - Ratu Alfiyatul Bariyah; Zakiyah, Rofiatun; Rahmat Supriyatna (Journal of Public Health Education, 2025)
Introduction: Patient satisfaction with community health center services is related to good guarantees, service quality and responsiveness. Dissatisfaction with service procedures and the comfort of the service environment can make patients not return to the health center and have a big influence on the satisfaction of outpatients at the health center. Objectives: The aim of this research is to determine the relationship between the queuing system and optimization of health services on patient satisfaction at the Cipayung Community Health Center, Depok City in 2024. Method: Quantitative research method with a cross sectional research design. The population in this study was 300 outpatients at the health center at one time. The sample test used was using the Slovin formula and a sample of 75 samples was obtained. The data used is primary data distributed through a questionnaire. Data analysis was carried out univariate and bivariate using the Chi-Square test. Result: Based on the research results, it shows that there is a relationship between the queuing system, p-value = 0.015 (p<0.05), there is a relationship between optimizing health services, p-value = 0.008 (p<0.05) with patient satisfaction at the Cipayung Community Health Center, Depok City. Conclution: The conclusion of this research is that there is a relationship between the queuing system and optimizing health services on patient satisfaction at the UPTD of Cipayung Health Center, Depok City in 2024.